2023
DOI: 10.24294/jipd.v7i1.2127
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating environmental performance through green human resource practice: Does green transformational leadership matter?

John Wiredu,
Qian Yang,
Shadi Saljoughipour
et al.

Abstract: Businesses are essential in nations’ economic development, green practice, and environmental performance, particularly in emerging countries. Such economic development needs environmental-friendly business practices to attain higher environmental performance goals of businesses. Nevertheless, a plethora of studies centered on the direct effects of environmental management initiatives (EMI) and green innovation practices (GIP) on environmental performance (EP). Still, the direct and indirect impacts of green hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 63 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…It was discovered that government consumption had a considerable positive link with economic performance. Population expansion was discovered to be beneficial [32] .…”
Section: Income Tax and Economic Performancementioning
confidence: 99%
“…It was discovered that government consumption had a considerable positive link with economic performance. Population expansion was discovered to be beneficial [32] .…”
Section: Income Tax and Economic Performancementioning
confidence: 99%
“…Accordingly, environmentally friendly practices and operations bring competition and cooperative advantages, resulting in a rise in economic success and competitiveness (Karia, 2020). Thus, businesses must advance their abilities to manage and control the EP regarding their actions to tackle stringent organizational protocols alongside growth in consumer demand (Ramanathan et al, 2017;Wiredu, Yang, Saljoughipour, et al, 2023). Furthermore, Jum'a et al (2021) observed that GSCM practices remain fresh in several production businesses.…”
Section: Introductionmentioning
confidence: 99%